Green Building Concept with The World’s Largest Seismic Isolated Hospital in Turkey - Kemal Solak (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
Certification systems used to test green buildings have become popular nowadays. In addition, there has been a gradual increase in the involvement of the players in the construction sector and public awareness of sustainability. These systems, which are useful in mitigating the building's environmental impacts, reveal difficulties in their implementation, especially for devoloping countries. Because of the problems affecting the population, such as air pollution and health problems, most world states came together and held conferences to take joint binding decisions. In Turkey, Leadership in Energy and Environmental Design (LEED) is first on the total number of certified green buildings, followed by the Building Research Establishment Environmental Assessment Method (BREEAM) and the German Sustainable Building Council (DGNB). This article summarizes the methodology used by some of these rating methods, shows a comparative approach between these rating systems, and provides an overview of how green building relates to sustainable development practices. Lastly, the building of the hospital was analyzed using  LEED certification system as a case study and the differences in the results were evaluated.